2017
DOI: 10.1038/s41467-017-02062-6
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of early light signaling by the carboxy-terminal output module of Arabidopsis phytochrome B

Abstract: Plant phytochromes are thought to transduce light signals by mediating the degradation of phytochrome-interacting transcription factors (PIFs) through the N-terminal photosensory module, while the C-terminal module, including a histidine kinase-related domain (HKRD), does not participate in signaling. Here we show that the C-terminal module of Arabidopsis phytochrome B (PHYB) is sufficient to mediate the degradation of PIF3 specifically and to activate photosynthetic genes in the dark. The HKRD is a dimerizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
92
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(95 citation statements)
references
References 82 publications
(200 reference statements)
2
92
0
1
Order By: Relevance
“…1a). The OPM contains two PAS-related domains (PAS-A, PAS-B) and a Histidine Kinase Related Domain (HKRD) and is required for phytochrome dimerization (Nagatani, 2010;Qiu et al, 2017). The OPM contains two PAS-related domains (PAS-A, PAS-B) and a Histidine Kinase Related Domain (HKRD) and is required for phytochrome dimerization (Nagatani, 2010;Qiu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…1a). The OPM contains two PAS-related domains (PAS-A, PAS-B) and a Histidine Kinase Related Domain (HKRD) and is required for phytochrome dimerization (Nagatani, 2010;Qiu et al, 2017). The OPM contains two PAS-related domains (PAS-A, PAS-B) and a Histidine Kinase Related Domain (HKRD) and is required for phytochrome dimerization (Nagatani, 2010;Qiu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Because PB localization requires the dimeric Pfr:Pfr form of phyB 43,46 , the thermostability of a PB is likely determined by the stability of the Pfr:Pfr dimers in the PB. Consistent with this notion, our results showed that the thermosensitivity of PBs is determined by the N-terminal photosensory module of phyB.…”
Section: Discussionmentioning
confidence: 99%
“…The dynamics of PBs have been characterized extensively using transgenic lines expressing phyB-FP 36,39,40,[44][45][46]54,55 , and therefore, to examine the dynamics of phyB-FP PBs induced by temperature changes, we went back to the phyB-FP lines, including PBG (phyB-GFP), which expresses functional phyB-GFP to complement the null phyB-5 mutant in the Landsberg erecta (Ler) background 36 , and PBC (phyB-CFP), which expresses phyB-CFP to complement the null phyB-9 mutant in Col-0 46,55 . Because both PBG and PBC overexpress phyB-FP 36,55 , we first examined whether they retain the same temperature effects as their respective ecotype background.…”
Section: Tissue/organ-specific Temperature Effects On Phyb Signalingmentioning
confidence: 99%
See 2 more Smart Citations